Children’s Literature in Constitutional Period and Khalil Hamid’s Works for Children - Beyhan Kanter (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
The Constitutional Monarchy period is an era when children’s literature began to develop as a separate field and publications for children heightened. Khalil Hamid, who was a graduate of Darulfunun and a teacher for many years and a writer of stories for children in this period, is also among the authors who contributed to the development of children’s literary culture. Being one of the authors of both the Ottoman and Republican periods, he also wrote popular love novels, stories for children, detective novels, and works related to women’s rights and family life, especially during the years of the Constitutional Monarchy. The author’s writing activities in this period have been seen in magazines, especially for women and children. Although his works on women’s rights and detective novels have been cited as references, no studies have been conducted on his life, literary personality, and works written for children. This article unleased the information about Khalil Hamid’s literary personality, who has not been conducted any academic study related to him. Also, children’s books selected as sample will be examined in terms of pedagogical, aesthetic, thematic, and fictional perspective by considering characteristics of children’s literature in Constitutional Period.